A Swedish national twin study of criminal behavior and its violent, white-collar and property subtypes. Issue 11 (4th May 2015) - Kendler, K. S.; Maes, H. H.; Lönn, S. L.; Morris, N. A.; Lichtenstein, P.; Sundquist, J.; Sundquist, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Background We sought to clarify the etiological contribution of genetic and environmental factors to total criminal behavior (CB) measured as criminal convictions in men and women, and to violent (VCB), white-collar (WCCB) and property criminal behavior (PCB) in men only. Method In 21 603 twin pairs from the Swedish Twin Registry, we obtained information on all criminal convictions from 1973 to 2011 from the Swedish Crime Register. Twin modeling was performed using the OpenMx package. Results For all criminal convictions, heritability was estimated at around 45% in both sexes, with the shared environment accounting for 18% of the variance in liability in females and 27% in males. The correlation of these risk factors across sexes was estimated at +0.63. In men, the magnitudes of genetic and environmental influence were similar in the three criminal conviction subtypes. However, for violent and white-collar convictions, nearly half and one-third of the genetic effects were respectively unique to that criminal subtype. About half of the familial environmental effects were unique to property convictions. Conclusions The familial aggregation of officially recorded CB is substantial and results from both genetic and familial environmental factors. These factors are moderately correlated across the sexes suggesting that some genetic and environmental influences on criminal convictions are unique to men and to women. Violent criminal behavior and property crime are substantially influenced respectively by genetic and shared environmental risk factors unique to that criminal subtype.